Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/j.2161-1912.2012.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style Differences and Depression in African American and European American College Women: Normative Adaptations?

Abstract: This study examined ethnic differences in attachment styles and depression among African American and European American college women. African American women reported less favorable views of others, which suggests that attachment styles emphasizing caution in relationships may be normative and adaptive for these women. There were no differences between groups in views of self or reports of depressive symptoms. implications for long-term relationships and counseling are discussed.Este estudio examinó las difere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Our results further supported the notion that cultural practices influence attachment styles (Keller, 2013) and the relationship between attachment styles and adjustment (Cooley & Garcia, 2012). Researchers view psychological development as a function of cultural practices and biological systems (e.g., Greenfield et al, 2003 Markus & Kitayama, 1991; Miller, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our results further supported the notion that cultural practices influence attachment styles (Keller, 2013) and the relationship between attachment styles and adjustment (Cooley & Garcia, 2012). Researchers view psychological development as a function of cultural practices and biological systems (e.g., Greenfield et al, 2003 Markus & Kitayama, 1991; Miller, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…As noted by previous researchers (e.g., Cooley & Garcia, 2012; Keller, 2013; Rothbaum et al, 2000 and as tested in the Turkish and German samples in the present study, attachment orientations showed some variations across cultures. In addition, our findings provide support for the cultural moderation hypothesis in that culture moderated the relationship of attachment orientations and psychological distress.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations